2014
DOI: 10.1002/anie.201403582
|View full text |Cite
|
Sign up to set email alerts
|

Flow‐Based Enzymatic Ligation by Sortase A

Abstract: Sortase-mediated ligation (sortagging) is a versatile, powerful strategy for protein modification. Because the sortase reaction reaches equilibrium, a large excess of polyglycine nucleophile is often employed to drive the reaction forward and suppress sortase-mediated side reactions. A flow-based sortagging platform employing immobilized sortase A within a microreactor was developed that permits efficient sortagging at low nucleophile concentrations. The platform was tested with several reaction partners and u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
46
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(47 citation statements)
references
References 83 publications
0
46
0
1
Order By: Relevance
“…Owing to the unfavourable kinetics of wild-type SrtA, efficient bioconjugation typically requires equimolar concentration of substrate and enzyme. Iterated rounds of FACS screening with increasing stringency produced evolved variants of SrtA (eSrtA) with 140-fold higher k cat /K m values, enabling new applications [78][79][80][81][82][83] .…”
Section: Positive Screeningmentioning
confidence: 99%
“…Owing to the unfavourable kinetics of wild-type SrtA, efficient bioconjugation typically requires equimolar concentration of substrate and enzyme. Iterated rounds of FACS screening with increasing stringency produced evolved variants of SrtA (eSrtA) with 140-fold higher k cat /K m values, enabling new applications [78][79][80][81][82][83] .…”
Section: Positive Screeningmentioning
confidence: 99%
“…SrtA staph has also been covalently immobilized on sepharose or PEGA resins to facilitate enzyme removal and enzyme recycling [14, 32]. A useful extension of sortase-immobilization has been the construction of flow-based systems in which reactants are passed over immobilized sortase columns [14, 33]. The flow-based reactor described by Pentelute and coworkers is particularly noteworthy in that the authors demonstrated that flow-based sortagging increased isolated product yields, and reduced contamination by hydrolytic, cyclic, or oligomeric by-products relative to analogous reactions performed using a standard solution-phase protocol [33].…”
Section: Optimizing Srtastaph Performancementioning
confidence: 99%
“…Indeed, sortagging reactions conducted under dialysis conditions or in centrifugal filtration units can significantly enhance reaction conversion through selective removal of low molecular weight aminoglycine by-products [3538]. Similarly, affinity immobilization strategies combined with sortase-substrate fusions or the aforementioned flow-based sortagging platform have been shown to minimize the need for excess reagents through the selective removal of various reaction components [27, 33]. All of these approaches are straightforward, and typically do not require changes in the sortase substrate recognition site.…”
Section: Driving Ligation Product Formationmentioning
confidence: 99%
“…Pentelute and coworkers designed a flow-based process that allows the use of lower concentrations of nucleophile without degradation of product yield. 49 Liu and coworkers chose to evolve SrtA using a yeast display technology, which lead to a mutant with 140-fold greater activity over wild type. 50 A subsequent evolution project resulted in two new SrtA mutants with altered sequence specificity (LPXSG and LAXTG).…”
Section: Peptide Tags For Protein Labelingmentioning
confidence: 99%